Assistance in Understanding and Implementing School Rules to Build National Character in Elementary Madrasah Students of Madarikul Huda Cigoong Mekarsari - Khariza Rizka Fadhilah; Muhammad Al Mighwar; Lyra Amelia; Ajani Fikri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This empowerment aims to analyze the understanding and implementation of student discipline in Madrasah Ibtidaiyah (MI) Madarikul Huda. The background of this empowerment and research arose from concerns about student discipline and the level of compliance with school rules. The quantitative research method was used by collecting data through a survey of 31 students regarding their understanding and implementation of the school rules. The results showed that the majority of students had a good understanding of the rules and tried to comply with the existing rules. However, some students have not fully complied with some aspects of the discipline, such as applicable norms and rules regarding food/drink in the classroom. Nonetheless, the survey results reflect the potential for improvement in students' awareness and understanding of the importance of school discipline. This research underscores the need for collaboration between schools, teachers, and parents to shape student character by fostering the values of discipline, responsibility, and ethics.